Favorable anatomic and visual outcomes with 25-gauge vitrectomy for myopic foveoschisis - Mii M (Dove Medical Press, 2014)
Mei Mii, Masato Matsuoka, Kayako Matsuyama, Yayoi Otsu, Tetsuya Nishimura Department of Ophthalmology, Kansai Medical University, Takii Hospital, Osaka, Japan Purpose: To report the surgical outcomes of 25-gauge vitrectomy in eyes with myopic foveoschisis (MF). Methods: The medical records of 40 eyes of 36 patients that had undergone 25-gauge vitrectomy with internal limiting membrane peeling for MF were studied. The main outcome measures were the best-corrected visual acuity (BCVA) and the optical coherence tomography (OCT) findings. The eyes were divided into two groups: 1) those with a foveal detachment (FD; FD group); and 2) those without a FD (no-FD group). Results: The postoperative OCT images showed a resolution of the MF with a significant reduction in the central foveal thickness from the preoperative values in both the FD group (479±150 µm to 196±56 µm; P=0.002, mean ± standard deviation) and in the no-FD group (369±116 µm to 245±50 µm; P=0.001). The final mean BCVA significantly improved from the preoperative values in the FD group (0.96±0.53 logarithm of the minimum angle of resolution [logMAR] units to 0.70±0.56 logMAR units; P=0.009) and in the no-FD group (0.46±0.38 logMAR units to 0.34±0.36 logMAR units; P=0.007). The final BCVA in the FD group improved in 63%, remained unchanged in 31%, and worsened in 6%. In the no-FD group, the final BCVA improved in 21%, remained unchanged in 71%, and worsened in 8% of the eyes. A better final BCVA was significantly correlated with a better preoperative BCVA in both groups (P<0.001). Conclusion: Twenty five-gauge vitrectomy results in favorable visual and anatomic outcomes for MF. We recommend that 25-gauge vitrectomy be used to treat eyes with MF. Keywords: myopic foveoschisis, 25-gauge vitrectomy, high myopia, internal limiting membrane, gas tamponade